1968
DOI: 10.1126/science.161.3842.700
|View full text |Cite
|
Sign up to set email alerts
|

Olefins of High Molecular Weight in Two Microscopic Algae

Abstract: The hydrocarbon composition of two algae, a golden-brown (Bot-ryococcus braunii) and a blue-green (Anacystis montana), has been investigated by gas chromatography-mass spectrometry. Both show distributions of aliphatic hydrocarbons of odd carbon numbers in the medium and high ranges of molecular weight, with maxima at n-C(17) and n-C(29) for B. braunii and n-C(17) and n-C(29) for A. montana. With the exception of the n-heptadecane of A. montana all the hydrocarbons are monoenes, dienes, or trienes. Since certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Three distinct races of B. braunii have been described based on the types of hydrocarbons that each accumulates (2). Race A accumulates fatty acid-derived alkadienes and alkatrienes (3), race L accumulates the tetraterpene lycopadiene (4), and race B accumulates triterpenes, predominately botryococcene, squalene, and their methylated derivatives (5). The oils accumulate both in intracellular oil bodies and in association with an extracellular matrix (6), which in race B consists largely of long-chain, cross-linked biopolymers formed in part from acetalization of polymethylsqualene diols (7).…”
mentioning
confidence: 99%
“…Three distinct races of B. braunii have been described based on the types of hydrocarbons that each accumulates (2). Race A accumulates fatty acid-derived alkadienes and alkatrienes (3), race L accumulates the tetraterpene lycopadiene (4), and race B accumulates triterpenes, predominately botryococcene, squalene, and their methylated derivatives (5). The oils accumulate both in intracellular oil bodies and in association with an extracellular matrix (6), which in race B consists largely of long-chain, cross-linked biopolymers formed in part from acetalization of polymethylsqualene diols (7).…”
mentioning
confidence: 99%
“…For example, monoenoic hydrocarbons were found in the biodiesel made form Chlamydomonas and Limnothrix. Unsaturated hydrocarbons are known to be produced by algae, [4][5]11 and saturated hydrocarbons were identified in Nostoc and Limnothrix. These types of compounds are the major constituents of liquid fuels (e.g., gasoline and diesel) and may therefore be important for biofuel production.…”
Section: Methodsmentioning
confidence: 99%
“…Short-chain n-alkenes (<n-C22) can derive from cyanobacteria, microalgae, macroalgae and zooplankton, while long-chain n-alkenes (>n-C22) are traditionally thought to be derived from either higher plant waxes (Eglinton and Hamilton, 1967) or microalgae (e.g. Gelpi et al, 1968Gelpi et al, , 1970Cardoso et al, 1983, Jaffé et al, 1996Volkman et al, 1998). Because of these different possible origins, the distribution of nalkenes in lacustrine sediment records often leads to disparate interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria can contain a wide range of n-alkenes (e.g. Gelpi et al, 1968;1970;Cardoso et al, 1983): species include Oscillatoria sp., which contains n-C21:1 to n-C23:1 alkenes (Matsumoto et al, 1990) and Anacystis montana, common in eutrophic lakes, is reported as a source of n-C19 to n-C29 alkenes (Gelpi et al, 1968). Gelpi et al (1968;1970) detected predominantly n-C25:1 and n-C27:1 alkenes in A. montana, but this finding is disputed by Murray and Thomson (1977) since their axenic A. montana cultures contained no long-chain n-alkenes at all.…”
Section: Stable Carbon Isotopic Compositionmentioning
confidence: 99%